The safety and serious adverse events of approved ALK inhibitors in malignancies: a meta-analysis - Hou H (Cancer Management and Research, 2019)
Helei Hou,* Dantong Sun,* Kewei Liu, Man Jiang, Dong Liu, Jingjuan Zhu, Na Zhou, Jing Cong, Xiaochun ZhangDepartment of Medical Oncology, The Affiliated Hospital of Qingdao University, Qingdao University, Qingdao, People’s Republic of China*These authors contributed equally to this workBackground: A total of 2%–7% of non-small cell lung cancer (NSCLC) patients have anaplastic lymphoma kinase (ALK) mutations. At present, three or more generations of ALK inhibitors have been used for ALK-positive NSCLC treatment, including crizotinib, alectinib, ceritinib, and brigatinib. Although most adverse events (AEs) of ALK inhibitors are grades 1 to 2 and generally can be well tolerated, serious adverse events (SAEs) of ALK inhibitors lack data analysis, and the lung toxicity of ALK inhibitors needs attention. Thus, we performed this meta-analysis to evaluate the safety of ALK inhibitors, especially in terms of drug-related SAEs.Methods: A total of 19 studies from 4 databases (PubMed, Science Direct, ClinicalTrials.gov and Cochrane Library) were included in this meta-analysis. All statistical analyses in this meta-analysis were performed with the STATA 14.0 software. We analyzed the incidences of total AEs, total SAEs and SAEs for different ALK inhibitors.Results: AEs of the ALK inhibitors occurred in almost all participants, and SAEs occurred in more than 20% of the participants. For ceritinib and brigatinib, SAEs occurred in more than 40% of the participants. Alectinib is most likely the safest of the two generations of ALK inhibitors. Generally, the ALK inhibitors showed significant lung toxicity.Conclusion: In conclusion, attention should be focused on ALK inhibitor-related SAEs, especially lung toxicity. According to this meta-analysis, alxectinib seems to be the safest ALK inhibitor. Physicians should focus on the related SAEs when prescribing ALK inhibitors.Keywords: ALK inhibitors, safety, serious adverse events, lung toxicity